A MicroRNA Expression Signature as Prognostic Marker for Oropharyngeal Squamous Cell Carcinoma. (15th October 2020) - Liu, Xinyi; Liu, Ping; Chernock, Rebecca D; Yang, Zhenming; Lang Kuhs, Krystle A; Lewis, James S.; Luo, Jingqin; Li, Hua; Gay, Hiram A; Thorstad, Wade L; Wang, Xiaowei
Abstract: Background: Improved prognostication of oropharyngeal squamous cell carcinoma (OPSCC) may facilitate individualized patient management. The goal of this study was to develop and validate a prognostic signature based on microRNA sequencing (miRNA-seq) analysis. Methods: We collected tumor specimens for miRNA-seq analysis from OPSCC patients treated at Washington University in St Louis (n = 324) and Vanderbilt University (n = 130). OPSCC patients (n = 79) from The Cancer Genome Atlas Program were also included for independent validation. Univariate and multivariable Cox regression analyses were performed to identify miRNAs associated with disease outcomes. All statistical tests were 2-sided. Results: By miRNA-seq profiling analysis, we identified a 26-miRNA signature. Based on computed risk scores of the signature, we classified the patients into low- and high-risk groups. In the training cohort, the high-risk group had much shorter overall survival compared with the low-risk group (hazard ratio [HR] = 3.80, 95% confidence interval [CI] = 2.37 to 6.10, P < .001). Subgroup analysis further revealed that the signature was prognostic for HPV-positive OPSCCs (HR = 3.07, 95% CI = 1.65 to 5.71, P < .001). Multivariable analysis indicated that the signature was independent of common clinicopathologic factors for OPSCCs. Importantly, the miRNA signature was a statistically significant predictor of overall survival in independent validation cohorts (The Cancer Genome Atlas Program cohort: HR = 6.05, 95% CI = 2.10 to 17.37, P < .001; Vanderbilt cohort: HR = 7.98, 95% CI = 3.99 to 15.97, P < .001; Vanderbilt HPV-positive cohort: HR = 8.71, 95% CI = 2.70 to 28.14, P < .001). Conclusions: The miRNA signature is a robust and independent prognostic tool for risk stratification of OPSCCs including HPV-positive OPSCCs.